Audit Rekam Kesehatan Elektronik - Tri Purnama Sari; Wen Via Trisna (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2013)
ABSTRACTThe information technology development in Indonesia give impact on healthrecords system athealth care facility by used electronic syatem. The Electronic health records selected due to easeand speed up management service of patient data. This impact can be seen from many cases instudent final report at Medical Record Vocational School UGM. It ‘s many diferent system ofElectronic Health Records used in many health care facilities, from a limited enrollment of patientdata until electronical system.It requiredspeciallegal rulesgoverningthe implementation ofelectronic healthrecordsin health care.The rules arethe basis forthe legaluseof electronic healthrecordsinIndonesia.In additionitisnecessary toguaranteethe use ofelectronichealthrecordimplementationaccreditationstandard.Accreditationcan bedone byan independent agencyappointedby governmentagenciesbothnationalandrefers to a systemof internationallyaccreditedhealthcarerecords.Keywords: audit, healthrecord, electronic, accreditation